Dyadic effects of type D personality and perceived control on health-related quality of life in cardiac arrest survivors and their spouses using the actor–partner interdependence model. (April 2020) - Israelsson, Johan; Persson, Carina; Bremer, Anders; Strömberg, Anna; Årestedt, Kristofer
Background: There is a lack of knowledge about factors associated with health-related quality of life in cardiac arrest survivors and their spouses. In addition, survivors and spouses are likely to affect each other's health-related quality of life. Aims: The aim was to investigate if a distressed personality and perceived control among cardiac arrest survivors and their spouses were associated with their own and their partner's health-related quality of life. Methods: This dyadic cross-sectional study used the actor–partner interdependence model to analyse associations between a distressed personality (type D personality), perceived control (control attitudes scale), and health-related quality of life (EQ index and EQ visual analogue scale). Results: In total, 126 dyads were included in the study. Type D personality and perceived control in cardiac arrest survivors were associated with their own health-related quality of life. In their spouses, a significant association was found for type D personality but not for perceived control. In addition, type D personality and perceived control in survivors were associated with health-related quality of life in their spouses. Conclusions: Type D personality and perceived control are factors that might be considered during post cardiac arrest, because of the associations with health-related quality of life in survivors and spouses. More research is needed to test psychosocial interventions in the cardiac arrest population in order to improve health-related quality of life.